Reactive oxygen intermediates are involved in the induction of CD95 ligand mRNA expression by cytostatic drugs in hepatoma cells - Hug, Hubert; Strand, Susanne; Grambihler, Annette; Galle, Jan; Hack, Volker; Stremmel, Wolfgang; Krammer, Peter H.; Galle, Peter R. (The journal of biological chemistry, 1997)
Oxidative stress has been associated with the induction of programmed cell death. The CD95 ligand/receptor system is a specific mediator of apoptosis. We have used the model of drug-induced apoptosis to assess whether the CD95 ligand mRNA is induced by reactive oxygen intermediates. Treatment of HepG2 hepatoma cells with bleomycin induced the production of reactive oxygen intermediates and, as an additional parameter of oxidative stress, resulted in glutathione (GSH) depletion. In parallel, CD95 ligand mRNA expression was induced. In a similar fashion CD95 ligand mRNA expression increased after treatment with H2O2. Additional treatment with the antioxidant and GSH precursor N-acetylcysteine resulted in partial restoration of intracellular GSH levels and in reduced induction of CD95 ligand mRNA. Induction of CD95 ligand mRNA by bleomycin was further reduced by combined treatment withN-acetylcysteine and deferoxamine. These data suggest a direct role of oxygen radicals in the induction of the CD95 ligand.